Role Of Islamic Universities In Enhancing The Right To Education Of Females - Badamasiuy, Juwayriya Bint (Advances in Social Sciences Research Journal, 2015)
Islam makes the acquisition of knowledge compulsory on all the Muslims, regardless of sex, thereby making education a right of every Muslim. Yet Female education is one of the most neglected areas of educational planning and practice in most predominantly Muslim societies, and hence the Muslim females are denied the right and access to education. Most Islamic universities all over the world have formulated law and policies to promote and encourage female education in line with the objective of Islam and the law. This article used arm chair research method and doctrinal analyses to examine the right of women to education under the Islamic law. The article then examined some contemporary gender policies and proposes the formulation of sound policies to be implemented by the existing Islamic Universities in Nigeria in line with the general Islamic conception of gender as it is practiced and adopted by Islamic universities worldwide. This is with the view to promoting the access of female to education